Students’ emerging pedagogical reflexivities in respect of their "student teacherly becoming" on a PGCE Diversity and Inclusivity module - Feldman, J.A.; Fataar, A. (South African Journal of Higher Education, 2020)
Situated in the context of teaching in higher education, the article provides a discussion on how student teachers in a Post Graduate Certificate of Education (PGCE) module mediate their ‘teacherly becoming’ (Author 2012) as pre-service teachers. The article presents the argument that learning to become a professional teacher involves not only what the students are learning, but also who they are becoming. The data for the article is drawn from student assignments which invited students to draw on the module readings and class discussions to consider their positioning as intentional/unintentional bearers of the past. The assignment required of them to consider how their emerging reflexivities as student teachers are influenced by their personal and educational backgrounds, and how these affected their ‘becoming’ as student teachers in the PGCE programme. The data is presented and discussed on the basis of four themes that emerged from the student essays. The article concludes by suggesting that modules that prepare student teachers for the complexity of the teaching profession and interaction with their students will be more productive if opportunities are provided in the module’s assessment modalities, for the students to reflexively engage with aspects of their ‘being and becoming’ as pre-service teachers.